Penerapan Model Pembelajaran Kooperatif Tipe Numbered Head Together Untuk Meningkatkan Keterampilan Berpikir Kritis Siswa SD Negeri 29 Ambon: Indonesia - Aziz, Rizki Amelia; Ritiauw, Leonid; Ritiauw, Samuel P. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the application of the numbered head together cooperative learning model to improve the critical thinking skills of fifth-grade elementary school students. This study used a quantitative research design with a pre-experimental design. The sample used in this study consisted of 20 fifth-grade students at SD Negeri 29 Ambon. The data collection techniques used were observation, tests and documentation. Meanwhile, the data analysis techniques used were the N-Gain test, and Normality test. The results showed that: 1) the application of the cooperative learning model type (NHT) was very effective in the learning process, 2) there was an increase in students' critical thinking skills in social studies using the application of the cooperative learning model type (NHT).